Skazani-rodzice. Sytuacja prawna osadzonych sprawujących opiekę nad dziećmi - Kwieciński, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article analyses the provisions of the Executive Criminal Code in terms of the legal status of persons who have children under the age of 18 and who have been sentenced to imprisonment. Under the Polish model of conduct with this category of prisoners, the Legislator has tried to develop a comprehensive and modern legal framework. These efforts have resulted in three different rules of conduct depending on the circumstances related to the prisoner and the needs of his or her children. Assuming that the regulations referred to in this article will become amended, the law institutions described here may be expected to properly achieve the aims set for them, in particular as regards the maintenance of family relations. Maintaining ties with family members has been deemed to be one of the fundamental rights of prisoners. Such contacts are also said to play an important role in the process of social re-adaptation of prisoners.
Keywords: więzień; zakład karny; kara pozbawienia wolności; rodzice; dzieci; opieka; prawo do kontaktów z rodziną